United States’s Intevention against the Islamic State of Iraq and the Levant - Indri Susilo; Rizqi Apriani Putri; Nur Azizah (Indonesian Association for International Relations, 2018)
ABSTRACTCombating terrorism is one of the foreign policy of the United States (US). The Islamic State of Iraq and The Levant (ISIL) or The Islamic State of Iraq and Syria (ISIS) is one of the movement deemed terrorists and has disturbed world peace. Ultimately the US decided to intervene to deal with the frequent acts of terror by ISIS which resulted in gross human rights violations.This article aims to find out how the US intervention to combat human rights abuses and acts of terror that have been done by ISIS.The method in this article was to do library research in the form of books, articles, journals and various media relevant in this article.It has been found that the form of settlement efforts to reduce human rights violations, the US made preventive and repressive efforts. In preventive efforts, the US created an international coalition to gain support to counter terror committed by ISIS. Then the repressive effort is humanitarian intervention in the form of military aid and humanitarian aid. The US donates 1.2 billion annually and 350 million dollars as a form of military and humanitarian aid to combat ISIS. Keywords: Humanitarian Interventions, Human Rights Violations, International Coalition, United States Intervention